RATIONALE FOR MODIFICATION OF CLASSIFICATION OF PULPITIS - T.P. Skripnikova; L.M. Khavalkina; S.I. Heranin; S.V. Bilous (Ukrainian Medical Stomatological Academy, 2017)
Among a large number of classifications of pulpitis there is no such that would reflect the peculiarities of pulpitis from all sides of this disease. The authors identified the causative factors of disease, clinic, development, processes occurring in the pulp of the tooth. But still nobody managed to characterize everything in a particular systematization (neither domestic nor foreign authors). We offer our own version. And welcome to the debate.